An electrophysiological study on children and young adults with Alport's syndrome. Issue 1 (January 1994) - Jeffrey, B G; Jacobs, M; Sa, G; Barratt, T M; Taylor, D; Kriss, A
Abstract : Alport's syndrome is characterised by progressive haematuric nephritis and high tone sensorineural hearing loss. Ocular signs are variable, the most consistent findings being anterior lenticonus and retinal flecks in the macula and mid peripheral areas. Previous electrophysiological studies on patients with Alport's syndrome have mostly been on adult patients undergoing haemodialysis, or after renal transplantation. A group of young patients with Alport's syndrome were studied to assess if early electrophysiological changes were detectable. A total of 20 patients (15 males and five females) between the ages of 3.5 and 22 years (mean 12.7 (years) were examined and compared with control subjects. Visual evoked potentials and electroretinograms were obtained following flash and pattern reversal stimulation. Electro-oculograms were also recorded. No significant electrophysiological changes were found in any of the 20 patients, including four who had visible fundus changes.